Hemodynamic Disorders in Explosive Mine Injury: Experimental Study - V. N. Yelsky; G. K. Krivobok; A. N. Talalayenko; A. A. Redko; A. Yu. Kryuk (Общая реаниматология)
The authors have studied hemodynamic features in explosive mine injury in the presence or absence of a preliminary exposure to premorbid mining factors. A combined influence of premorbid mining factors following an explosive mine injury has been ascertained to induce more severe systemic and cerebral hemodynamic disorders than an isolated explosive mine injury.